Endonasal Skull Base Tumor Removal Using Concentric Tube Continuum Robots: A Phantom Study - Swaney, Philip J.; Gilbert, Hunter B.; Webster, Robert J., III; Russell, Paul T., III; Weaver, Kyle D. (Journal of Neurological Surgery Part B: Skull Base, 2015)
Objectives The purpose of this study is to experimentally evaluate the use of concentric tube continuum robots in endonasal skull base tumor removal. This new type of surgical robot offers many advantages over existing straight and rigid surgical tools including added dexterity, the ability to scale movements, and the ability to rotate the end effector while leaving the robot fixed in space. In this study, a concentric tube continuum robot was used to remove simulated pituitary tumors from a skull phantom.Design The robot was teleoperated by experienced skull base surgeons to remove a phantom pituitary tumor within a skull. Percentage resection was measured by weight. Resection duration was timed.Setting Academic research laboratory.Main Outcome Measures Percentage removal of tumor material and procedure duration.Results Average removal percentage of 79.8 ± 5.9% and average time to complete procedure of 12.5 ± 4.1 minutes (n = 20).Conclusions The robotic system presented here for use in endonasal skull base surgery shows promise in improving the dexterity, tool motion, and end effector capabilities currently available with straight and rigid tools while remaining an effective tool for resecting the tumor.
Keywords: skull base; endoscopic; transnasal; pituitary; Cushing adenoma; surgical robotics; robot; concentric tube continuum robot; active cannula